Prevalence of diabetes mellitus, hypertension, and obesity and their correlation with quality of life among elderly people living in old age homes of Kamrup, Assam - Talukdar, Kakali; Barthakur, Chinmayee; Bharali, Mintu D.; Ojah, Jutika (International Journal Of Community Medicine And Public Health, 2024)
Background: The world population is rapidly ageing due to increased longevity and decreased mortality rates. The United Nations has declared 2021-2030 as the decade of healthy ageing. To attain this concept, the ultimate goal is to improve the quality of life (QoL) of elderly people by early detection and prevention of complications of non-communicable diseases. Changes in family structure and psycho-social values in today's era often compel the elderly to shift to old age homes (OAHs). Thus, this study aimed to estimate the prevalence of type 2 diabetes mellitus, hypertension, and obesity in the elderly living in OAHs and their correlation with QoL. Methods: A community-based cross-sectional study was conducted at the OAHs of Kamrup (M), Assam for twelve months. A sample of 300 elderly living in OAHs was selected and data was collected using a pre-designed, pre-tested schedule. All the respondents were screened and evaluated for diabetes mellitus, hypertension and obesity. Their quality of life was assessed using WHOQOL-BREF and correlated with blood pressure, blood sugar values and anthropometric indicators. Results: The prevalence of type 2 diabetes mellitus, hypertension and obesity were found to be 32.33%, 37% and 37.33% respectively. On spearman rank correlation the relation between blood pressure, random blood sugar values and anthropometric indicators with QoL was found to be significant. Conclusions: This high prevalence necessitates the adoption of various strategies to combat the burden, promote healthy lifestyle behaviour and provide proper care with counselling to improve the QoL in elderly.